COMPUTER DETERMINATION OF KINEMATIC PARAMETERS OF THE MECHANISM WITH TWO ROCKER GROUPS USING THE KDAM PROGRAM - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; MELNIK, GENADIJ; KIRICHENKO, ANTON; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The use of the KDAM computer program made it possible to determine the kinematic parameters of the mechanism with two rocker groups of winding machines, which made it possible to determine the coordinates, projections of the speeds and accelerations of the hinges and the points of attachment of the links of the second rocker group Asura and, on the basis of this, to choose rational parameters of the structural links of the mechanism for ensuring the necessary law of movement of the holes of the working elements of the winding production machines. The kinematic study of the complex mechanism was performed in three stages. At the first stage, the kinematic parameters of the input link were determined. On the second, the kinematic parameters of the first rocker group were determined. After that, the kinematic parameters of the point were reassigned and the kinematic parameters of the second rocker group were determined. The obtained results are used in the program to assess the tension of the technological processes of winding production when determining the change in the relative tension of the thread during the formation of cylindrical packages. Kinematic analysis of complex flat mechanisms of winding production machines, which include rocker groups, plays a significant role in choosing rational parameters of the structural links of the mechanism to ensure the necessary law of movement of the openings of the working elements of winding production machines. The use of the KDAM computer program, which is the development of the authors of this article, allows you to determine the kinematic parameters of the hinges and the connection points of the links of the second rocker group of Asura winding machines, which allows you to choose rational parameters of the structural links even at the design stage. The results of these studies can be used to optimize the design parameters of mechanisms and minimize energy consumption. The use of the KDAM computer program made it possible to determine the kinematic parameters of the mechanism with two rocker groups of winding machines, which made it possible to determine the coordinates, projections of the speeds and accelerations of the hinges and the points of attachment of the links of the second rocker group Asura and, on the basis of this, to choose rational parameters of the structural links of the mechanism for ensuring the necessary law of movement of the holes of the working elements of the winding production machines. The kinematic study of the complex mechanism was performed in three stages.